Theories of school counseling for the 21st century - Dollarhide, Colette T.; Lemberger-Truelove, Matthew E. 1976- (Oxford University Press, 2019)
"This unique book offers readers a compilation of contemporary and cutting-edge theories to inform the way school counselors practice the art and science of school counseling. Readers will gain tremendous insight into each theory, helping with selection of a favorite theory or contribute to theoretical flexibility for the school counseling practitioner"--Provided by publisher.